Predominant period and amplification factor estimation with respect to geomorphology - a case study of Sylhet city corporation area, Bangladesh - Hossain, Md Shakhawat; Kamal, ASM Maksud; Rahman, Md Zillur; Rahman, Md Mostafizur; Nahar, Kamrun; Woobaidullah, ASM (Bangladesh Journal of Scientific Research, 2016)
Predominant period and amplification factor of the subsurface soils of Sylhet city corporation area have been estimated using microtremor. Their relation to the geomorphological units of the city has been determined. The estimated predominant periods of alluvial fan, back swamp, flood plain, isolated hills, level hills, piedmont plain, point bar and ridge of the city are 0.60, 0.75, 0.73, 0.23, 0.62, 0.45, 0.73 and 0.66 sec., respectively. With maximum (± 0.88) and minimum (± 0.38) standard deviation amplification factor of alluvial fan, back swamp, flood plain, isolated hills, level hills, piedmont plain, point bar and ridge are 3.1, 4.1, 4.6, 3.75, 2.22, 4.12, 4.18 and 4.42, respectively. According to amplification seismic hazard of different geomorphological units of the city has been ranked from very low to relatively high hazard zone whereas level hill falls under very low, alluvial fan under low, flood plain under relatively high and back swamp, isolated hills, piedmont plain, point bar and ridge falls under moderate hazard zone. Bangladesh J. Sci. Res. 27(1): 1-10, June-2014